Studi Literatur: Perencanaan Pajak Penghasilan Angsuran Pasal 25 - Evriansyah, Evriansyah; Herna, Herna; Pahala, Indra (Department of Public Administration, 2023)
Effective tax planning is a form of efficiency in corporate income tax burden so as to reduce the amount of installments for article 25 tax payments. The purpose of this study is to find out how effective and efficient tax planning is based on the use of article 25 income tax. This study uses a systematic method to review relevant literature, namely the systematic literature review (SLR) method. The application of this methodology aims to identify, study, evaluate, and interpret related data presented with emerging and interrelated questions. To obtain similar research relevant to the topic, this study uses keywords: tax planning, income tax installments article 25. There are five literature reviews that approach research topics for 2021 and 2022. The results of this study found that each entity has different tax planning according to the type and conditions of the business being run, but has a positive impact, namely efficiency in tax costs so that monthly tax installments become smaller and help companies manage their cash flow.